Simulation of Solar Energetic Particle Events Originated from Coronal Mass Ejection Shocks with a Data-driven Physics-based Transport Model - Lei Cheng; Ming Zhang; Ryun Young Kwon; David Lario (The Astrophysical Journal)
Solar energetic particle (SEP) events are associated with coronal mass ejections (CMEs) and/or solar flares. SEPs travel through the corona and interplanetary space to reach Earth, posing a radiation hazard to spacecraft and astronauts working in space and the electronics on spacecraft. Due to the distinct magnetic field configuration and solar eruption kinematic properties associated with each event, the use of a data-driven model becomes essential for predicting SEP hazards. In this study, we use a developed model that utilizes photospheric magnetic field measurements and CME-driven shock observations as inputs to simulate several historical SEP events associated with fast CME speeds (>700 km s ^−1 ). The model includes an SEP source term aligned with the theory of diffusive shock acceleration by the CME-driven shock. The performance of the model is assessed by comparing simulations and observations of SEP intensity-time profiles at Solar and Heliospheric Observatory, ACE, STEREO-A, and STEREO-B. The results generally match the observations well, particularly for protons below 40.0 MeV. However, discrepancies arose for higher-energy protons, notably for the events on 2011 March 7 and 2014 February 25, where the simulation tends to overestimate the proton flux. At STEREO-A, the modeled proton intensities for the SEP events on 2013 April 11 and 2011 March 7 display a very different behavior compared to observations because of the efficient transport in longitude caused by the weak magnetic field.